Long term variation of an amphipod species’ population secondary production as indicator of incomplete resilience in a temperate estuary - Leite, Nuno (2014)
During the last decades many estuaries underwent ranges of environmental pressure due to increasing anthropogenic pressures and the undertaken of mitigation measures to prevent the impoverishment of these areas. The Mondego estuary (NW Atlantic coast of Portugal), a mesotidal shallow estuary, is one typical case of this. In the 1980s, the system was characterized by rich and stable animal and vegetal communities, with no eutrophication symptoms (pre-eutrophication period), whereas during the 1990s, massive seasonal macroalgal blooms were observed and the concomitant adverse consequences on the system’s biodiversity were registered (eutrophication period). More recently (2000–2010), eutrophication symptoms have gradually decreased due to several mitigation actions, whilst recent studies indicate that the system is recovering in terms of biodiversity and structure (post-mitigation period). The population dynamics and productivity of Echinogammarus marinus (Leach) (Amphipoda, Gammaridae), a key species associated to fucoids in many Northern Atlantic estuaries, was analyzed and compared throughout these three distinct periods in the Mondego estuary, using data collected between April 2009 and March 2010 and data from the 1980s (pre-eutrophication) and 1990s (eutrophication period). The goal of this study was to test if the long-term variation of E. marinus would somehow reflect the range of environmental conditions observed in the system from the 1980s until 2010. Results showed that, in the three different periods, the species exhibited higher densities during spring, with continuous sexual activity throughout the year, multivoltine life cycle and seasonal sex-ratio fluctuations. Moreover, salinity was a major factor affecting the amphipod population in all three periods. On the other hand, differences related to the production of E. marinus were detected, being clearly higher in the 1980s (pre-eutrophic period), followed by the last decade (post-mitigation period) and, finally, the 1990s (eutrophication period), where population production and density values were the lowest of all three periods. These results suggest that E. marinus production parameters reflected the decline in environmental conditions during the 1990s, as well as the partial recovery resulting from the application of mitigation measures, exhibiting a good sensitivity to environmental pressures, namely eutrophication. Therefore, we propose that in the last years, the Mondego estuary has been under an incomplete resilience period, characterized by some environmental improvement compared to the 1990s but still distant from the 1980s condition. Overall, E. marinus production parameters seem to be good indicators of the system’s environmental condition and might be useful regarding monitoring programmes in most Northern Atlantic estuaries.